ANALYSIS ON THE PURCHASING DATA TO RE-DESIGN THE PROCEDURE OF TURNAROUND MAINTENANCE - Winda Nur Cahyo; Buchairi Zaman (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2020)
Turnaround (TA) is a large-scale maintenance activity (extraordinary maintenance activities), which is carried out periodically (repeated large-scale maintenance), where the work referred to can only be carried out when the unit is stopped operating. The main scope of work is inspection (inspection), repair, cleaning equipment. The success or failure of turnaround activities is very influential from careful preparation, some of the failures of turnaround activities result from unplanned preparations. One factor is the readiness of the material. This paper discusses the direct involvement of the material procurement process in determining better TA preparation time. The historical data from the purchasing is analyses and then the result is combined with the new proposed procedure of the TA maintenance. The new procedure has three months less than the current procedure.